2015
DOI: 10.1111/aas.12674
|View full text |Cite
|
Sign up to set email alerts
|

A simple method for isocapnic hyperventilation evaluated in a lung model

Abstract: It is possible to maintain isocapnia during HV by delivering carbon dioxide through a standard anaesthesia circuit equipped with modern monitoring capacities. From alveolar ventilation, CO2 production and dead space, the amount of carbon dioxide that is needed to achieve IHV can be estimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…The delivered amount of CO 2 (DCO 2 ) was manually regulated via a high precision mechanical flow meter (1-1000 ml/min) originally used for NO distribution and recalibrated for CO 2 (Nomius M, used in a multicentre study by Lundin et al 1999). 9,16 (Fig. 1) Isocapnia was defined as a return to baseline FETCO 2 value.…”
Section: Experimental Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…The delivered amount of CO 2 (DCO 2 ) was manually regulated via a high precision mechanical flow meter (1-1000 ml/min) originally used for NO distribution and recalibrated for CO 2 (Nomius M, used in a multicentre study by Lundin et al 1999). 9,16 (Fig. 1) Isocapnia was defined as a return to baseline FETCO 2 value.…”
Section: Experimental Protocolmentioning
confidence: 99%
“…9 The method is based on a non-rebreathing technique without the need to disconnect the anaesthesia circle system. 9 The method is based on a non-rebreathing technique without the need to disconnect the anaesthesia circle system.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The delivered CO 2 flow (DCO 2 ) was manually regulated through a high‐precision mechanical flow metre (1–1000 ml/min) originally used for NO distribution (Nomius M) (Figure ) . In a previous bench study, we calculated the flow of CO 2 needed to achieve stable isocapnia using this standardized hyperventilation procedure and constructed a nomogram of DCO 2 according to gender and weight . In each patient of this pilot study, the flow metre was set to an individual flow of CO 2 using this nomogram.…”
Section: Methodsmentioning
confidence: 99%
“…An IHV method, currently studied but not yet in clinical use, is to infuse CO 2 to the inspiratory limb of the breathing circuit through a mixing box. This technique was recently evaluated by us, in a bench test and in an in vivo model, using prototype equipment . Thus, it was shown that IHV was obtained by doubling baseline mechanical ventilation together with the delivery of CO 2 at a dose maintaining the FICO 2 level close to 3%.…”
mentioning
confidence: 99%